ANALISIS PERSEPSI AKUNTAN INDONESIA TERHADAP AKUNTANSI LINGKUNGAN - Febrianto, Irwan; Ethika, Ethika; Yunilma, Yunilma; Rifa, Dandes; Helmawati, Helmawati (Jurnal Kajian Akuntansi dan Auditing, 2025)
Environmental accounting is an important element in corporate reporting as a form of responsibility for the impact of business activities on the environment. However, environmental accounting practices in Indonesia are still diverse and not optimal, and accountants' attention to this issue is considered low. This study aims to analyze the perceptions of the accounting profession, namely auditors, accounting educators, and corporate accountants, regarding the basic concepts, disclosures, and measurements of environmental accounting. Data were collected through the distribution of Google Form-based questionnaires via WhatsApp and analyzed using the Kruskal-Wallis test. The results showed that there was no significant difference in perception between respondent groups regarding the basic concepts and disclosures of environmental accounting. However, there was a difference in perception in terms of measurement, where accounting educators tended to believe more that environmental costs could be measured in monetary units, compared to auditors and corporate accountants. This difference is likely due to a stronger theoretical approach in accounting educators, while practitioners face constraints in measurement validity. This study reinforces the urgency of preparing environmental accounting standards that can be applied widely and consistently in Indonesia